Identification of Cacao Mild Mosaic Virus (CaMMV) and Cacao Yellow Vein-Banding Virus (CYVBV) in Cocoa (Theobroma cacao) Germplasm - Ihsan Ullah (MDPI AG, 2021)
Cocoa, Theobroma cacao, is an important tropical perennial crop grown widely in the humid tropics. The exchange of cocoa germplasm between germplasm collections and breeding centres is vital for varietal development. Intermediate quarantine facilities, such as the International Cocoa Quarantine Centre, Reading UK (ICQC-R) play a vital role in ensuring the transfer of germplasm whilst minimising the risk of spreading pests and diseases. Current screening procedures combine visual inspection and molecular techniques, which are effective in detecting Cocoa swollen shoot virus (CSSV), a badnavirus, which causes severe losses but are restricted to West Africa. However, the detection of latent or mild virus infections that produce no visual symptoms has been a challenge. Recently two badnavirus species of cocoa producing mild symptoms, cacao mild mosaic virus (CaMMV) and cacao yellow vein-banding virus (CYVBV), have been sequenced. Here, we report new assays for the detection of these two species, for the first time in non-symptomatic accessions. Evolutionary and bioinformatic analyses of the viruses suggest their most recent source was from Trinidad, though there is historic evidence that these viruses may have their origin in South America and then become widespread globally over the last century. We also report a novel colorimetric Loop-mediated isothermal amplification (LAMP) assay for the detection of CYVBV. This simple and accurate method could be employed in field virus testing.